Overview of IgG4-Related Tubulointerstitial Nephritis and Its Mimickers - Hyeon Joo Jeong; Su-Jin Shin; Beom Jin Lim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Tubulointerstitial nephritis (TIN) is the most common form of renal involvement in IgG4-related disease. It is characterized by a dominant infiltrate of IgG4-positive plasma cells in the interstitium and storiform fibrosis. Demonstration of IgG4-positive plasma cells is essential for diagnosis, but the number of IgG4-positive cells and the ratio of IgG4-positive/IgG-positive plasma cells may vary from case to case and depending on the methods of tissue sampling even in the same case. IgG4-positive plasma cells can be seen in TIN associated with systemic lupus erythematosus, Sjögren syndrome, or anti-neutrophil cytoplasmic antibody-associated vasculitis, which further add diagnostic confusion and difficulties. To have a more clear view of IgG4-TIN and to delineate differential points from other TIN with IgG4-positive plasma cell infiltrates, clinical and histological features of IgG4-TIN and its mimickers were reviewed. In the rear part, cases suggesting overlap of IgG4-TIN and its mimickers and glomerulonephritis associated with IgG4-TIN were briefly described.